(3JfHjg GdCOjH GdZQjHs - (3CMeO Hf GdMSjf Hf GdMSf Hf YHO GdUeO GdcfOj GdeJfHj, CHh GdWjH,J (B254 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdMQef GdQMje MeOkG def CQTOfG dMSf EJHGY COH fHjg hHYO aGdeLO dG jeO SQGOb GdCYdi ef Mdi HOQ GdCOH LjO aVGFdg s
(3BNQgG (B:s
(3haVVfG ef eTcdGJ cdGeg eSc GdNJGe hGdMeO ddg hcai hSdGe Ydi YHGOg GdPjf EUWai Je gPG GdcJGH HYhf Gdedc GdhgGH hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNJGf s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs